FETAL AND MATERNAL OUTCOME IN MAJOR DEGREE PLACENTA PREVIA - Mahnaz Raees; Zeenat Parveen; Mustafa Kamal (Gomal Journal of Medical Sciences, 2015)
Background: Placenta previa is associated with significant maternal and fetal morbidity and mortality. This study was conducted to determine the feto-maternal outcome of pregnancies complicated by major degree placenta previa. Material & Methods: This cross-sectional study was conducted at Department of Gynaecology & Obstetrics, Lady Reading Hospital, Peshawar, Pakistan, from March 25, 2007 to March 24, 2008. Fifty pregnant, ultrasonographically confirmed cases of major degree placenta previa were assessed for maternal and fetal outcome of pregnancies. Results: The mean age of patients was 29.98+7.15 years. Maximum number of cases 26(52%) were in 21-30 years age group. Regarding gravidity 28(56%) were multigravida, 9(18%) grand multigravida, 8(16%) great grand multigravida and 5(10%) primigravida. Regarding parity 25(50%) were multipara, 9(18%) grand multipara, 6(12%) primipara, 5(10%) great grand multipara and 5(10%) nullipara. Gestational age at presentation was in 24(48%) as 33-36 weeks, 19(38%) at 37-40 and 7(14%) at 28-32 weeks. Regarding fetal outcome, 42(84%) neonates were alive and 8(16%) dead. Birth weight ranged from 1.8 to 4 kg mean 2.75+0.58. Regarding APGAR score, 34(68%) had >7, 8 (16%)